2015
DOI: 10.1038/jhh.2015.44
|View full text |Cite
|
Sign up to set email alerts
|

Individual 6-year systolic blood pressure change and impact on cardiovascular mortality in a French general population

Abstract: Impact of blood pressure (BP) visit-to-visit variability remains controversial for untreated hypertensives and for normotensive subjects. Association between 6-year systolic BP change and all-cause and cardiovascular (CVD) mortality was studied in general primary care population including untreated hypertensive and normotensive subjects. Normotensive individuals and untreated high BP patients (40,926 and 14,283, respectively) had two check-ups (interval: 5.8±2.2 years) at the IPC center (Paris). Follow-up was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
1
0
2
Order By: Relevance
“…Data from the Minnesota Business and Professional Men Study (n=261) and the Zutphen Study were shown, and the 10-year BP trajectory was the strongest predictor of cardiovascular mortality and all-cause mortality in Minnesota [19]. Cardiovascular health studies concluded that long-term visit-to-visit SBP variability was independently associated with a higher risk of subsequent mortality and a meta-analysis of 13 cohort studies in Japan also presented that adjusted mortality increased with increasing BP [20, 21]. These studies found that BP changes are a powerful predictor of cardiovascular events independently of mean SBP or DBP, which is more common in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the Minnesota Business and Professional Men Study (n=261) and the Zutphen Study were shown, and the 10-year BP trajectory was the strongest predictor of cardiovascular mortality and all-cause mortality in Minnesota [19]. Cardiovascular health studies concluded that long-term visit-to-visit SBP variability was independently associated with a higher risk of subsequent mortality and a meta-analysis of 13 cohort studies in Japan also presented that adjusted mortality increased with increasing BP [20, 21]. These studies found that BP changes are a powerful predictor of cardiovascular events independently of mean SBP or DBP, which is more common in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Схожие результаты получены исследователями многих стран мира. Так, согласно данным 6-летнего исследования, проведенного во Франции, риск смерти от всех причин у лиц с повышенным САД в 1,31 раза выше, чем у лиц с нормальным АД, а от ССЗ -в 2,51 раза [8]. В Иранском когортном исследовании установлено, что вероятность смерти от всех причин и от ССЗ увеличивается пропорционально увеличению АД [9].…”
Section: Discussionunclassified
“…Наши результаты согласуются с данными многих крупных исследований, выявивших высокие показатели ОР среди курящих и у лиц, страдающих АГ [8,9]. Кроме того, многие исследователи сообщают о существовании тесной взаимосвязи между АГ и курением и о наличии экспоненциального усиления их отрицательного влияния на кардиоваскулярную систему при их сочетании [10].…”
Section: обсждениеunclassified